Bauhaus : Dessau, Chicago, New York. - Danilowitz, Brenda; Eskildsen, Ute; James-Chakraborty, Kathleen; Junker, Susanne; Keitel, Hans-Peter; Koehler, Karen; Költzsch, Georg-W.; Lavin, Maud; Margolin, Victor; Möller, Werner; Thöner, Wolfgang; Tupitsyn, Margarita; et al. (Köln : DuMont, 2000)
Albers, Anni ; Albers, Josef ; Altschuler, Franz ; Arndt, Alfred ; Barford, George ; Bayer, Herbert ; Bayer, Irene ; Breuer, Marcel ; Caldwell, Alfred ; Carter, Peter ; Chermayeff, Serge ; Edson, Danforth, George ; Feininger, Andreas ; Feininger, Lyonel ; Feininger, T. Lux ; Fieger, Carl ; Filipowski, Richard ; Finberg ; Fischer, Vories ; Fletcher, Norman ; Friedman, William ; Goldsmith, Myron ; Gropius, Walter ; Haid, David ; Halberstadt, Milton ; Hall, Lillian ; Harkness, J. ; Hilberseimer, Ludwig ; Kandinsky, Wassily ; Keck, William ; Kendall, Jean ; Kepes, Gyorgy ; Klee, Paul ; Kozman, Myron ; Kroll, Boris ; Kuhr, Fritz ; Leckie, Hubert ; Lerner, Nathan ; Levstik, Frank ; Lindenfeld, Lore Kadden ; Longini, Robert ; Lustig Cohen, Elaine ; Lustig, Alvin ; Malcolmson, Reginald ; Mies van der Rohe, Ludwig ; Moholy, Lucia ; Moholy-Nagy, Laszlo ; Noland, Kenneth ; Page, Don ; Peterhans, Walter ; Platt, Norman ; Pritikin, Max ; Rauschenberg, Robert ; Reiss, Hilde ; Riley, Dorothy ; Schawinsky, Xanti ; Siegel, Arthur ; Smith, Tony ; Tague, Robert Bruce ; Testa, Angelo ; Uhlmann, Ilse ; Weininger, Andor ; Woelffer, Dina ; de Patta, Margaret
biog. 298-308
Duits
Bauhaus : Dessau, Chicago, New York, Museum Folkwang Essen, 12. August bis 12. November 2000
boek
Keywords: Chicago; Dessau; New York